Ethics in medical decision making: an intercultural outlook - BERESTOVA, A.V; ORLOV, S. A.; GORENKOV, R. V; STAROSTIN, V. P. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT In the climate of globalization, the choice dilemma is complicated by ethical conflicts that exist in multicultural contexts. This article investigates the capacity criteria across cultures and the boundaries of delegating responsibility for the patient’s health to other people. The attitude towards euthanasia was taken as a marker to trace differences. Statistical analysis of euthanasia acceptability in 2017 involved Western civilizations, according to Huntington. The analysis showed a high prevalence of euthanasia in the Netherlands (48%) and the lowest prevalence in the United States (2%) and Canada (2%). Religious beliefs have a direct effect on ethics in decision making. RESUMEN En el clima de globalización, el dilema de elección se complica por los conflictos éticos que existen en contextos multiculturales. Este artículo investiga los criterios de capacidad entre culturas y los límites de delegar la responsabilidad de la salud del paciente a otras personas. La actitud hacia la eutanasia se tomó como un marcador para rastrear las diferencias. El análisis estadístico de la aceptabilidad de la eutanasia en 2017 involucró a las civilizaciones occidentales según Huntington. El análisis mostró una alta prevalencia de eutanasia en los Países Bajos (48%) y la prevalencia más baja en los Estados Unidos (2%) y Canadá (2%). Las creencias religiosas tienen un efecto directo sobre la ética en la toma de decisiones.